Doxorubicin and NFL-TBS.40-63 peptide loaded gold nanoparticles as a multimodal therapy of glioblastoma - Myriam El Moutaoukil; Maria Grazia Lolli; Stefania D’Amone; Memona Khan; Roberta Grillo; Joel Eyer; Maddalena Grieco; Ornella Ursini; Jolanda Spadavecchia; Barbara Cortese (Discover Nano)
Abstract Conventional treatments for glioblastoma (GBM) are hindered by systemic toxicity, limited blood–brain barrier penetration, and therapeutic resistance. To address these challenges, we developed dual-functionalized gold nanoparticles (AuNPs) conjugated with a biotinylated NFL-TBS.40-63 peptide and the chemotherapeutic agent doxorubicin. This platform integrates targeted delivery and therapeutic action to enhance efficacy while minimising off-target effects. Our findings reveal superior cellular uptake, dose- and time-dependent cytotoxicity, and apoptosis induction in GBM cells compared to mono-functionalized counterparts. Furthermore, pH-sensitive drug release profiles underscore the system’s potential to exploit the tumour microenvironment’s acidic conditions for precise drug delivery. Comprehensive characterisation confirmed the stability, biocompatibility, and functional efficacy of the dual-functionalized AuNPs. This study highlights the promise of these nanoconjugates as a multimodal approach to GBM therapy, paving the way for further translational research in nanomedicine.